Relationship between social anxiety, loneliness, and life satisfaction among first year students at Universiti Putra Malaysia - Madon, Zainal; Wan Mohamad, Syed Hadi Imanudin (Universiti Putra Malaysia, 2024)
First year students are the people who need to be focused on the context of life Satisfaction because at this age, they are transitioning from adolescence to adulthood whereby can be one of the most stressful times in person’s life. This study aims to determine the relationship between social anxiety, loneliness, and life satisfaction among first year students in Universiti Putra Malaysia. 360 first year students between ages 19 t0 26 years old were selected using the cluster sampling technique. In this study, there were 3 types of instrumentation used to measure the variables related to the research which were The Liebowitz Social Anxiety Scale (LSAS) (Michael Liebowitz,1987) to measure social anxiety, UCLA Loneliness Scale (UCLA)(Daniel Russel,1996) to measure loneliness and The Satisfaction with Life Scale (SWLS)(Diener, Emmnos,Larsen & Griffin,1985)was used to measure life satisfaction. Data was collected using an online platform which was a Google form survey. In accordance with the aim and objectives of this research, two types of analysis which are univariate analysis (descriptive statistics) and bivariate analysis (Pearson correlation analysis and t-test) were used by using software SPSS VERSION 26. The results showed that social anxiety (r=-.320, p<0.05) has had significant negative relationship with life satisfaction of first year students. In addition, results found that loneliness (r=-.641, p<0.05) also had negative correlated with the life satisfaction of the first-year students and that there is no significant difference in life satisfaction between male and female (t=-.764, p>0.05). This study concluded that an increase in social anxiety, loneliness or both can lower the life satisfaction of the first-year student. These findings have positive social change implications and may be utilized to increase practitioner knowledge. Mental Health practitioners and professionals such as counselors, consultants and psychologists are encouraged to expand their knowledge and specialties in mental health issues in counselling. Government also needs to improve mental health policy and allocate resources to address the problems associated with social anxiety and loneliness.